IMPLEMENTASI EKSTRAKURIKULER QASIDAH DI MI MIFTAHUL HUDA I KOTA PALANGKA RAYA - Muyassarah; Naufal, Rahmad; Istiyati Mahmudah (Sasangga: Jurnal Pendidikan dan Pembelajaran, 2023)
The implementation of qasidah tambourine religious extracurricular activities is a kind of religious art, polite, relaxed and meaningful, and has many religious benefits that can be gleaned from the poetry and details of the prayer and the music. It can be said that extracurricular training can create added religious value for someone who takes part in the extracurricular activity, especially if the extracurricular is carried out by students who basically have to instill religious values in the construction process. The method used in this research is descriptive qualitative. Qualitative research is the process of collecting data through natural means with the aim of interpreting and analyzing phenomena which are the main tools of researchers. Qasidah extracurricular activities at MI Miftahul Huda I Palangka Raya City take place every Saturday after class with the extracurricular supervising teacher. Students play tambourines combined with qasidah songs/poems. A meeting of students participating in the qasidah extracurricular at MI Miftahul Huda in the city of Palangka Raya, a senior teacher teaches various rhythms, both on the Rebana musical instrument and on qasidah poetry